Efektivitas Permainan Kartu Kuartet dan Metode Menghafal - Hasnianti Hasnianti (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2019)
This study aims to compare the effectiveness of quartet card games and memorization methods for students' mastery of vocabularies. In this study, using quasi quantitative experiments. The sample of this study was purposive sampling taken from class VII A and B as many as 40 students with a population of 150 people. Then the data collection technique used by researchers is the evaluation test relating to the mastery of the consensus existing on the quartet card. The T-test is a formula that researchers use in obtaining research results. Obtained that the experimental class in this case class VII A, amounting to 19 students after treatment, then given a test obtained an average value of 5.8, while the control class, in this case, Class VII B students were 21 students after memorizing the vocabularies method. The same as the consensus in the quartet card and then given a test obtained an average value of 3,6, so it can be concluded that Ho is rejected and Ha is accepted because t arithmetic 4,23 is more significant than t table 1,68959.